2021 IEEE 34th International Symposium on Computer-Based Medical Systems (CBMS) 2021
DOI: 10.1109/cbms52027.2021.00087
|View full text |Cite
|
Sign up to set email alerts
|

A self-learning teacher-student framework for gastrointestinal image classification

Abstract: Medical data is growing at an estimated 2.5 exabytes per year [1]. However, medical data is often sparse and unavailable for the research community, and qualified medical personnel rarely have time for the tedious labeling work required to prepare the data. New screening methods of the gastrointestinal (GI) tract, like video capsule endoscopy (VCE), can help to reduce patients discomfort and help to increase screening capabilities. One of the main reasons why VCE is not more commonly used by medical experts is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…To achieve the main objective, seven datasets [23,24,25,26,27,28,29], 12 benchmark analysis studies and ML models to use with CAD systems [30,31,38,39,40,68,41,36,32,33,35,34] and eight GAN studies [72,73,77,74,70,67,75,76,71] were published to cover all the sub-objectives and finally achieve the main objective and answer the research question. Some of these papers contribute to multiple objectives, while others contribute to only a single objective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve the main objective, seven datasets [23,24,25,26,27,28,29], 12 benchmark analysis studies and ML models to use with CAD systems [30,31,38,39,40,68,41,36,32,33,35,34] and eight GAN studies [72,73,77,74,70,67,75,76,71] were published to cover all the sub-objectives and finally achieve the main objective and answer the research question. Some of these papers contribute to multiple objectives, while others contribute to only a single objective.…”
Section: Discussionmentioning
confidence: 99%
“…In the gastroenterology branch, classification models [30,31,32,33,34] to classify GI-tract findings and segmentation models [35,36] to segment polyp regions were investigated. When producing these ML solutions, we identified that generalizability is one of the main issues for both classification and segmentation due to the lack of labeled and annotated data to train ML models.…”
Section: Background and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…This network utilised double autoencoders for the segmentation of polyps. Gjestang et al proposed a teacher-student framework for the classification of GI diseases [ 30 ]. This network utilises unlabelled data for better generalisation.…”
Section: Related Workmentioning
confidence: 99%